2018
DOI: 10.1016/j.pocean.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric fluxes of soluble organic C, N, and P to the Mediterranean Sea: Potential biogeochemical implications in the surface layer

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 74 publications
9
27
2
Order By: Relevance
“…The relationship between monthly precipitation rates and DOC fluxes confirmed the high efficiency in DOM atmospheric deposition of DOC via rain events in the Med Sea, as recently reported by Djaoudi et al (2018).…”
Section: Doc Input From the Atmospheresupporting
confidence: 88%
See 1 more Smart Citation
“…The relationship between monthly precipitation rates and DOC fluxes confirmed the high efficiency in DOM atmospheric deposition of DOC via rain events in the Med Sea, as recently reported by Djaoudi et al (2018).…”
Section: Doc Input From the Atmospheresupporting
confidence: 88%
“…In addition, the Sahara desert is an intermittent source of mineral dust, that can transport nutrients and organic carbon to the Basin (Goudie and Middleton, 2001;Prospero et al, 2005;Vincent et al, 2016). Atmospheric deposition of nutrients (N and P) strongly influences the marine biogeochemical cycles of the Med Sea, it has therefore received attention in the last 30 years (Migon et al, 1989;Herut et al, 2002;Ridame and Guieu, 2002;Markaki et al, 2003Markaki et al, , 2010Pulido-Villena et al, 2008;Djaoudi et al, 2018). Compared to inorganic nutrients, there is still very few data on the atmospheric deposition of Dissolved Organic Carbon (DOC) to the surface ocean, both at the global and local scale.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean Sea, the existent dataset of nM measurements of DIP at both spatial and temporal scales is severely scarce. The few reported nM concentrations of DIP are limited to two cross-basin cruises (PROSOPE cruise in 1999, Moutin et al, 2002: 7 (Djaoudi et al, 2017). By reporting an important amount of vertical profiles along a longitudinal gradient, the present study is the first to extensively address the distribution of nM DIP in the P-depleted Mediterranean surface waters.…”
Section: Discussionmentioning
confidence: 75%
“…To date, lack of DIP data above this phosphacline has precluded resolving vertical variability in this key layer as has led to the traditional view of an entirely depleted and invariant dissolved phosphate surface pool. Few studies, however, by using sensitive determination of DIP, have reported low but detectable increases in nanomolar DIP concentration above the phosphacline adding evidence against this traditional view Krom et al, 2005;Djaoudi et al, 2017). Nevertheless, the scarcity and the sparse nature of available nM DIP data in the Mediterranean Sea still precludes a complete assessment of DIP dynamics in the upper waters at the basin scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation